Routing and Switching Essentials / Companion Guide - Empson Scott; Schmidt Cheryl; Cisco Networking Academy (2015)
This course describes the architecture, components, and operations of routers and switches in a small network. Introduction, Introduction to Switched Networks, Basic Switching Concepts and Configuration, VLANs, Routing Concepts, Inter-VLAN Routing, Static Routing, Routing Dynamically, Single-Area OSPF, Access Control Lists, DHCP, Network Address Translation for IPv4, Answers to the ''Check Your Understanding'' Questions, Glossary, Index.